Angiographic and Clinical Characteristics of Patients with Cerebral Arteriovenous Malformations Associated with Hereditary Hemorrhagic Telangiectasia - Matsubara, Shunji; Manzia, Jennifer L.; ter Brugge, Karel; Willinsky, Robert A.; Montanera, Walter; Faughnan, Marie E. (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: Cerebral arteriovenous malformations (AVMs) are occasionally associated with hereditary hemorrhagic telangiectasia (HHT), which is characterized by the presence of multiple mucocutaneous telangiectasia, epistaxis, and familial inheritance. We analyzed the angiographic and clinical characteristics of patients with cerebral AVMs related to HHT.METHODS: Among 638 patients with cerebral AVMs, we identified 14 patients with HHT. The AVMs were classified as those with nidi of 1 cm or less (micro AVMs), those with nidi between 1 and 3 cm (small AVMs), and those of the fistulous type (arteriovenous fistulas [AVFs]).RESULTS: A total of 28 AVMs were found; seven of 14 patients had multiple AVMs. The 28 AVMs were categorized as 12 micro AVMs, eight small AVMs, and eight AVFs. All except one micro AVM were asymptomatic, whereas all small AVMs were symptomatic. Three of eight AVFs were asymptomatic. All 28 AVMs were located on the cortex. All micro AVMs and AVFs had single feeders and single draining veins, whereas the small AVMs had multiple feeders in all lesions and single draining veins in six of eight lesions.CONCLUSION: Multiple, cortical, micro AVMs or AVFs harboring single feeding arteries and single draining veins should raise clinical suspicion of HHT-related AVMs.